Islamic Lifestyle on Hijab Alila YouTube Shows (Episode Bts the Series): Islamic Lifestyle Pada Tayangan YouTube Hijab Aila (Episode Bts The Series) - Fitri Nur Romadhan; Kukuh Sinduwiatmo (LPPM Stikosa - AWS, 2023)
The development of information technology, closely related to globalization, is evident in the significant enthusiasm of the public towards K-Pop and the fading of culture, as exemplified in the content showcased in the web series